TINGKAT LITERASI KEUANGAN PADA MAHASISWA S-1 FAKULTAS EKONOMI (Jurnal Manajemen dan Kewirausahaan, 2015)
The purpose of this research was to examine the level of financial literacy and the factors that influence undergraduate students of Faculty of Economics. This study distributed 625 questionnaires and only 584 usable questionnaires. Data analysis methods used by this research were descriptive statistics and ANOVA. The level of financial literacy was 48.91% were in the low category. The test results revealed that there was influence of gender, age, GPA, and parents income. The results showed that students should improve their understanding of personal finance, especially in the area of investment, in addition to the university to provide education about personal finance to students. Suggestions for further research was examined throughout the Trisakti University students, using online methods, increasing the number of questions and adding variables such as student income, savings and debt holdings and work experience students.